Aging Matters: A Multi-Site Study and Call to Action for Integrating Gerontological Content into Bachelor of Science, Associate Degree, and Practical Nursing Program Curricula. (Journal of Gerontological Nursing, 2025)
Purpose: The current study examined differences in senior nursing students' knowledge, attitudes, and perceived competency about older adults, based on enrollment in Bachelor of Science in Nursing (BSN), Associate Degree in Nursing (ADN), and Practical Nursing (PN) programs offering gerontological nursing curricula content. Method: A nonexperimental, descriptive survey design was used. A total of 145 senior nursing students from five pre-licensure programs in Florida completed a 92-item survey incorporating the Palmore Facts on Aging Quiz 2, Kogan's Attitudes Toward Old People Scale, and the Hartford Geriatric Nurse Competency Tool. Data were analyzed using analysis of variance (ANOVA), multivariate ANOVA, and Pearson correlation. Results: Students demonstrated limited knowledge about older adults but reported high perceived competency. A statistically significant difference in knowledge was found between program types, with PN students scoring highest. A moderate positive correlation existed between knowledge and attitudes. No significant differences were found for attitudes or perceived competency by program. Conclusion: The current study underscores the need to systematically design an evidence-based curriculum inclusive of gerontological nursing content across BSN, ADN, and PN programs to prepare the future nursing workforce to care for older adults.